Nurses and Inpatient Adolescents\' perceptions on Observance of privacy and its Importance - R Karimi; N Dehghan Nayeri; Z Daneshvar Ameri; A Mehran; T Sadeghi (Tehran University of Medical Sciences, 2009)
Background & Aim: Privacy is one of basic rights of the patients. Privacy becomes important for the adolescents when they hospitalize in an unfamiliar environment. This study aimed to compare the perceptions of inpatient adolescents with nurses on the observance of privacy and its importance. Methods & Materials: In this cross-sectional study, 175 nurses and a convenience sample of 180 inpatient adolescents who had met the inclusion criteria were recruited to the study. Data was gathered using a questionnaire. Man-whitney u and kruskal-wallis statistical tests were used to analyze the data. Results: The results showed that there was significant differences between nurses;apos and inpatient adolescents` perceptions on the observance of privacy and its importance (man-whitney u, P<0.001). The most important priority regarding the privacy from nurses;apos point of view was "covering the unnecessary parts of the body while caring" whilst it was "providing a pleasant decorated environment, telephone, toilet and bath in room, and hospitalization in a room with peers" from the adolescents;apos point of view. The most observed case about privacy from the nurses;apos point of view was "taking immediate action to help the teenagers if necessary" whilst, from the adolescents view, it was "calling them with their favorite names". Conclusion: The mean perceptions of nurses were higher than the adolescences toward observance of privacy and its importance. The results can guide nurses to improve quality of care for this group.